Review Article: Analysis of Emulsifier in Food Using Chromatographic Techniques - Rohman., Abdul; Che Man, Yaakob B; Noviana, Eka (Journal of Food and Pharmaceutical Sciences, 2013)
Emulsifiers so far are important class of additives used in food products. Food industries and regulatory authorities have striven for the continuous development of analytical methods to determine the emulsifiers in foods. Chromatography is one of the powerful analytical techniques used in the analysis of food components due to its capability for the separation and quantitative analyses of emulsifiers. This article describes some chromatographic techniques, namely gas chromatography (GC), high performance liquid chromatography (HPLC), supercritical fluid chromatography (SFC), and planar chromatography for detection and quantification of emulsifiers in food. Sample preparation involved in the analysis of emulsifiers has been also highlighted.